PENGARUH KEBIASAAN MEROKOK DAN POLA MAKAN PASIEN TERHADAP KEJADIAN HIPERTENSI PADA PASIEN RAWAT JALAN DI POLIKLINIK RUMAH SAKIT PATAR ASIH LUBUK PAKAM TAHUN 2021 - Juni Mariati Simarmata; Pitriani .; Samuel Ginting; Betti Susanti Tarigan; Yemima . (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
Hypertension or high blood pressure, sometimes also called arterial hypertension, is a chronic medical condition where the blood pressure in the arteries increases. The purpose of this study was to determine the effect of smoking habits and patient diet on the incidence of hypertension in outpatients at the hospital polyclinic Patar Asih Lubuk Pakam in 2020. The research method used a quantitative research design with a quasi experimental type. This research is a pre-experimental design using pre-test and final test. (the one group, pretest and post test design). The results obtained based on the analysis of the Paired T-test obtained p-value = 0.000 <a = 0.05, so the research hypothesis is accepted, so it can be concluded that there is an effect of smoking on the incidence of hypertension in outpatients at Patar Hospital. Asih Year 2020. Conclusion: Smoking habits before the incidence of hypertension, namely "not done" as many as 9 people (30.0%), smoking habits after the incidence of hypertension namely "not done" as many as 22 people (73.3%). Suggestion: It is hoped that this research can add input for further researchers to add research variables.